The “Old” and the “New” Antibiotics for MDR Gram-Negative Pathogens: For Whom, When, and How - Karaiskos, Ilias; Lagou, Styliani; Pontikis, Konstantinos; Rapti, Vasiliki; Poulakou, Garyphallia (Frontiers in Public Health, 2019)
The recent expansion of multidrug resistant and pan-drug-resistant pathogens poses significant challenges in the treatment of healthcare associated infections. An important advancement, is a handful of recently launched new antibiotics targeting some of the current most problematic Gram-negative pathogens, namely Carbapenem -producing Enterobacteriaceae (CRE) and Carbapenem-resistant P. aeruginosa (CRPA). Less options are available against carbapenem-resistant Acinetobacter baumannii (CRAB) and strains producing metallo-beta lactamases (MBL). Ceftazidime-avibactam signalled a turning point in the treatment of KPC and partly OXA- type carbapenemases, whereas meropenem-vaborbactam was added as a potent combination against KPC-producers. Ceftolozane-tazobactam could be seen as an ideal beta-lactam backbone for the treatment of CRPA. Plazomicin, an aminoglycoside with better pharmacokinetics and less toxicity compared to other class members, will cover important proportions of multi-drug resistant pathogens. Eravacycline holds promise in the treatment of infections by CRAB, with a broad spectrum of activity similar to tigecycline and improved pharmacokinetics. Novel drugs and combinations are not to be considered “panacea” for the ongoing crisis in the therapy of XDR Gram-negative bacteria and colistin will continue to be considered as a fundamental companion drug for the treatment of carbapenem-resistant Enterobacteriaceae (particularly in areas where MBL predominate), for the treatment of CRPA (in many cases being the only in vitro active drug) as well as CRAB. Aminoglycosides are still important companion antibiotics. Finally, fosfomycin as part of combination treatment for CRE infections and P. aeruginosa, deserves a greater attention. Optimal conditions for monotherapy and the “when and how” of combination treatments integrating the novel agents will be discussed.